Pengaruh Standar Operasional Prosedur (SOP) dan Pengawasan terhadap Kinerja Karyawan - Laela Rifa; Didip Diandra (JURNAL MANAJEMEN MOTIVASI, 2026)
Standard Operating Procedures (SOPs) are guidelines that every organization must have as a guide for the performance of work for each employee and are also useful for meeting and achieving desired work targets. This study aims to determine how standard operating procedures (SOPs) and supervision affect employee performance. This study uses a quantitative approach. The population in this study consists of 49 employees. The technique used is saturated sampling. The data collection technique in this study uses a statistical tool, namely SPSS 25. Based on the data processing results, a regression equation was obtained that describes the positive influence between Standard Operating Procedures and Employee Performance and the positive influence between Supervision and Employee Performance. Simultaneously, Standard Operating Procedures and Supervision affect Employee Performance. The coefficient of determination (R²) shows that the independent variables are able to influence the dependent variable by 74.9%, while the remaining 25.1% is influenced by other factors not discussed in this study.